Defect and temperature effects on the mechanical properties of kaolinite: a molecular dynamics study. (24th May 2019) - Yang, H.; Han, Z.F.; Hu, J.; He, M.C.
Abstract: Molecular dynamics simulations of different defective kaolinites under tension were performed to reveal the effects of defect location, type, density and temperature on their mechanical properties. Four types of defective kaolinite with Si vacancies were constructed. Based on the atomic-scale deformation and failure processes of defective kaolinite and its stress–strain curves, the Young's moduli and tensile strengths in three crystal directions were obtained and compared with the existing theoretical values from the literature. The defect location at each layer does not affect the mechanical properties of kaolinite and the cracks initiated at the defective sites. The atom density of each model was calculated in order to investigate the defect-type effect on the mechanical properties of kaolinite. The simulation results also showed that kaolinite exhibits brittle failure behaviour and the mechanical properties degrade significantly with increasing defect density and temperature. The influence of temperature on the mechanical properties of defective kaolinite is discussed in detail.